Anesthesiologists and Disaster Medicine: A Needs Assessment for Education and Training and Reported Willingness to Respond. (May 2017) - Hayanga, Heather K.; Barnett, Daniel J.; Shallow, Natasha R.; Roberts, Michael; Thompson, Carol B.; Bentov, Itay; Demiralp, Gozde; Winters, Bradford D.; Schwengel, Deborah A.
Abstract : BACKGROUND: Anesthesiologists provide comprehensive health care across the emergency department, operating room, and intensive care unit. To date, anesthesiologists' perspectives regarding disaster medicine and public health preparedness have not been described. METHODS: Anesthesiologists' thoughts and attitudes were assessed via a Web-based survey at 3 major academic institutions. Frequencies, percentages, and odds ratios (ORs) were used to assess self-reported perceptions of knowledge and skills, as well as attitudes and beliefs regarding education and training, employee development, professional obligation, safety, psychological readiness, efficacy, personal preparedness, and willingness to respond (WTR). Three representative disaster scenarios (natural disaster [ND], radiological event [RE], and pandemic influenza [PI]) were investigated. Results are reported as percent or OR (95% confidence interval). RESULTS: Participants included 175 anesthesiology attendings (attendings) and 95 anesthesiology residents (residents) representing a 47% and 51% response rate, respectively. A minority of attendings indicated that their hospital provides adequate pre-event preparation and training (31% [23–38] ND, 14% [9–21] RE, and 40% [31–49] PI). Few residents felt that their residency program provided them with adequate preparation and training (22% [14–33] ND, 16% [8–27] RE, and 17% [9–29] PI). Greater than 85% of attendings (89% [84–94] ND, 88% [81–92] RE, and 87% [80–92] PI) and 70% of residents (81% [71–89] ND, 71% [58–81] RE, and 82% [70–90] PI) believe that their hospital or residency program, respectively, should provide them with preparation and training. Approximately one-half of attendings and residents are confident that they would be safe at work during response to a ND or PI (55% [47–64] and 58% [49–67] of attendings; 59% [48–70] and 48% [35–61] of residents, respectively), whereas approximately one-third responded the same regarding a RE (31% [24–40] of attendings and 28% [18–41] of residents). Fewer than 40% of attendings (34% [26–43]) and residents (38% [27–51]) designated who would take care of their family obligations in the event they were called into work during a disaster. Regardless of severity, 79% (71–85) of attendings and 73% (62–82) of residents indicated WTR to a ND, whereas 81% (73–87) of attendings and 70% (58–81) of residents indicated WTR to PI. Fewer were willing to respond to a RE (63% [55–71] of attendings and 52% [39–64] of residents). In adjusted logistic regression analyses, those anesthesiologists who reported knowing one's role in response to a ND (OR, 15.8 [4.5–55.3]) or feeling psychologically prepared to respond to a ND (OR, 6.9 [2.5–19.0]) were found to be more willing to respond. Similar results were found for RE and PI constructs. Both attendings and residents were willing to respond in whatever capacity needed, not specifically to provide anesthesia. CONCLUSIONS: Few anesthesiologists reported receiving sufficient education and training in disaster medicine and public health preparedness. Providing education and training and enhancing related employee services may further bolster WTR and help to build a more capable and effective medical workforce for disaster response. Abstract : Supplemental Digital Content is available in the text.